Democracy satisfaction and political engagement: understanding student interest in political involvement - Patmisari, Patmisari; Haryani, Fenny Riza; Ariani, Sinta; Nur Isnaini, Dian Ratri (Jurnal Ilmiah Mimbar Demokrasi, 2024)
Trust will influence a person's choices, including selecting leaders. Therefore, this study wanted to see the influence of student democracy satisfaction on the interest in political involvement. This research utilizes a quantitative approach with a correlational design. The population of this research is all students from public and private universities since 2014/2015 who are in all areas of Java, using a proportional random sampling technique. The data analysis technique used is directed at testing the hypotheses that have been formulated. The research results from 272 re-spondents among students on the island of Java, and the first hypothesis shows that the t-value is 1.001 < 1.969 and the significance value is 0.318 > 0.05. The second hypothesis shows a t-value of 2.744 > 1.969 and a signifi-cance value of 0.006 < 0.05. The third hypothesis shows an F-count value of 4.212 > 3.049 and a significance value of 0.016 < 0.05. It can be concluded that there is no significant influence on the variable of student trust in gov-ernment and interest in political involvement. In contrast, the variable satis-faction with democracy on interest in political involvement has a significant influence. The influence that satisfaction with democracy has on interest in political involvement is positive. However, student trust in government and satisfaction with democracy influence interest in political involvement. The research results imply that satisfaction with democracy is an essential factor in efforts to increase interest in political involvement. The suggestion that is expected to provide material for consideration is that further research is needed on student satisfaction with democracy to determine student satisfac-tion with democracy.